Does Central Bank real policy rate affect inflation and economic activity? findings in the Philippines using SVAR models - Lacson, Donald Tristan L.; Jandoc, Karl Robert (Quezon City School of Economics, University of the Philippines Diliman, 2023)
This study addresses the deficiency in literature when it comes to determining the impact of real interest rate shocks toward aggregate output, inflation, and money supply in the Philippines through data obtained from the Bangko Sentral ng Pilipinas (BSP) and the Philippine Statistics Authority (PSA) from 2000Q1 to 2022Q2. Under the economic assumptions of rational expectations and central bank inflation targeting, a real policy interest rate measure was constructed in place of the nominal policy rate, which showed static movement over time, and proxy, non- policy rate, for a four-variable structural vector autoregression that controls for the structural break in output brought by the COVID-19 pandemic. Results show an inconclusive effect on aggregate output and money supply but a conclusive negative effect on inflation that could last up to 8 quarters after the policy interest rate shock. Inconclusive effect on aggregate output is conjectured to have been the result of a weak credit channel which may have been aggravated by the Asian Financial Crisis. Meanwhile, negative effect on inflation exhibited the “price puzzle” phenomenon and a couple of quarters lag which may have been a result of lag in inflationary expectations and the central bank’s level of credibility to target inflation. Granger causality tests were also conducted to determine if predictive or “granger” causality exists between the real policy rate and output, inflation, and money supply collectively. Results show uni-directional causality for most models, and bi- directional causality to some, indicating that movements of the real policy rate generally predict movements of other macroeconomic variables.
Thesis (BS Economics) - - University of the Philippines Diliman
Keywords: Central Bank of the Philippines; Interest rates; Inflation